(untitled) (Bangladesh Agronomy Journal, 2018)
A pot experiment on screening of wheat genotypes against drought stress was conducted at the research field of Sher-e-Bangla Agricultural University in earthen pots during rabi season of 2013-2014. Fifteen (15) wheat genotypes were evaluated under drought (stress was imposed by withdrawing irrigation after emergence) and well irrigated (control) condition. Exposure of plants to drought led to remarkable reduction in yield contributing characters which ultimate caused in reduced yield in all the genotypes. However, genotypes showed remarkable variability in yield reduction due to drought. The highest relative yield was observed in genotype SATYN-25 followed by SATYN-2, BARI Gom-26 and BARI Gom-28. However, yield reduction was less in SATYN-25 (about 20%) followed by BARI Gom-26 (21%) and SATYN-2 (25%). Besides yield performance of the genotypes, some drought tolerance indices like Geometric Mean Productivity (GMP), Stress Tolerance Index (STI), Yield Stability Index (YSI) and Stress Susceptible Index (SSI) were used to select the desirable genotypes. Among the genotypes, BARI Gom-26, BARI Gom-28 and SATYN-25 gave better yield with higher STI, GMP and YSI with lower SSI indicating that these genotypes would be suitable for growing under drought prone areas. Bangladesh Agron. J. 2017, 20(2): 97-105